2012
DOI: 10.1073/pnas.1115009109
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a toxic form of superoxide dismutase 1 protein to pathologically affected tissues in familial ALS

Abstract: Mutations in the gene encoding superoxide dismutase 1 (SOD1) account for about 20% of the cases of familial amyotrophic lateral sclerosis (fALS). It is not known how the mutant protein causes disease, or why only a subset of cell types (motor neurons) are targeted. The aggregation and misfolding of mutant SOD1 are implicated in disease pathogenesis in both animal models and humans. We used a monoclonal antibody, C4F6, which specifically reacts with mutant and/or "misfolded" SOD1, to investigate the regional di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
96
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 38 publications
6
96
0
Order By: Relevance
“…These small, soluble oligomers undergo aberrant interactions with cell machinery and activate cell death pathways, but their exact stoichiometry is not known and their properties have yet to be characterized. Recently, metastable soluble Cu,Zn superoxide dismutase (SOD1) oligomers have been identified that contain an epitope associated with disease-linked species of SOD1, mutants of which are implicated in a subset of ALS (15)(16)(17)(18). Size exclusion chromatography (SEC) of these oligomers revealed a size range of two to four monomers, consistent with previous findings of potentially cytotoxic SOD1 oligomers (19)(20)(21).…”
supporting
confidence: 69%
“…These small, soluble oligomers undergo aberrant interactions with cell machinery and activate cell death pathways, but their exact stoichiometry is not known and their properties have yet to be characterized. Recently, metastable soluble Cu,Zn superoxide dismutase (SOD1) oligomers have been identified that contain an epitope associated with disease-linked species of SOD1, mutants of which are implicated in a subset of ALS (15)(16)(17)(18). Size exclusion chromatography (SEC) of these oligomers revealed a size range of two to four monomers, consistent with previous findings of potentially cytotoxic SOD1 oligomers (19)(20)(21).…”
supporting
confidence: 69%
“…Furthermore, we observed the formation of inclusions in a small proportion of Sh-SY5Y cells treated with native SOD1 Wt , which were never present in NSC-34 cells. Metal-free forms of SOD1 have been proposed to be the toxic precursor preceding aggregation in familial aLS [43,44]. the majority of aLS mutations affect the structural stability of SOD1, leading to the exposure of buried hydrophobic residues, thus resulting in aggregation [45].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, accumulation of misfolded SOD1 has been reported by several groups also in sporadic ALS (27,(41)(42)(43)(44)(45)(46)(47), although other groups have reached the opposite conclusion (48)(49)(50)(51). The identification of MIF as a cytosolic chaperone that stimulates the folding or refolding of misfolded SOD1 and inhibits the aggregation of mutant SOD1 in vivo suggests new avenues for therapy in ALS, mediated by increasing intracellular MIF levels in the nervous system.…”
Section: Discussionmentioning
confidence: 99%